Translanguaging in Religious Speech: Practices, Evaluation, and Perception (International Journal of Culture and Art Studies, 2025)
Few studies have examined translanguaging's uses in preaching, which is the field of religious communication, even though it has been widely studied in educational communication. The study aims to characterize, evaluate, and perceive the translanguaging practices in Sunday sermons using Simalungun, a traditional language in North Sumatra Province. The study used a descriptive qualitative method with a survey design. Sixty priests participated in the study as participants selected by using a purposive sampling technique. Simalungun language was chosen as the language of sermon delivery, and the research instrument was the Google Form platform. This study found that motivation to employ translanguaging is crucial for effective sermon delivery and understanding. This study examines the reasons for priests' use of translanguaging, including the predominant preaching genre, the language used, challenges encountered, and congregational perceptions. The findings of this study provide a comprehensive account of translanguaging in Simalungun sermons, perceptions of the translanguaging practices, and better comprehension of messages in the sermon as implications of the study.  The study suggests that additional research on the content of preaching in Sunday sermons be conducted using various analytical methodologies.